2017
DOI: 10.1538/expanim.17-0028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-estradiol on cold-sensitive receptor channel TRPM8 in ovariectomized rats

Abstract: Transient receptor potential cation channel subfamily M member 8 (TRPM8) is associated with sensitivity to cold sensation in mammals. A previous study demonstrated that TRPM8 was overexpressed in the skin of ovariectomized (OVX) rats due to the loss of estrogen. In the present study, we investigated whether estrogen replacement restricts overexpression of the TRPM8 channel in the skin of OVX rats. We divided 15 Sprague Dawley rats into three groups: a non-operated group (NON-OPE), an ovariectomy group (OVX), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Estrogen also has been described to play a critical role in cold sensitivity and hyperalgesia [ 40 , 41 ], which are also functions thought to be regulated by Trpm8 [ 42 , 43 ]. However, interestingly, a previous preclinical study observed that Trpm8 expression was upregulated in the skin of ovariectomized rats compared to sham control rats [ 44 ] and β-estradiol treatment might reduce Trpm8 overexpression in the skin of ovariectomized rats [ 45 ]. These findings support our data that suggest regulation of energy metabolism in female mice is independent of Trpm8 cold-sensing function and estrogen might be a more relevant factor to normal thermoregulation in females.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen also has been described to play a critical role in cold sensitivity and hyperalgesia [ 40 , 41 ], which are also functions thought to be regulated by Trpm8 [ 42 , 43 ]. However, interestingly, a previous preclinical study observed that Trpm8 expression was upregulated in the skin of ovariectomized rats compared to sham control rats [ 44 ] and β-estradiol treatment might reduce Trpm8 overexpression in the skin of ovariectomized rats [ 45 ]. These findings support our data that suggest regulation of energy metabolism in female mice is independent of Trpm8 cold-sensing function and estrogen might be a more relevant factor to normal thermoregulation in females.…”
Section: Discussionmentioning
confidence: 99%
“…E2 did not affect TRPM8 mRNA expression in the spinal ganglia of ovariectomized rats treated with menthol, which means that TRPM8 expression did not affect the inhibitory action of E2 on menthol-induced hyperthermia. E2 induced a decreasing trend in TRPM8 mRNA expression, but did not affect the protein level in the lumbar skin of ovariectomized rats (5). TRPM8 mRNA and protein in the lumbar skin of ovariectomized rats were lower than those in sham rats after exposure to cold (4˚C, 20 min) (9).…”
Section: Discussionmentioning
confidence: 83%
“…First, we planned to investigate the TRPM8 protein that expressed after several hours after menthol stimulation; however, we dropped the idea because we could not obtain the appropriate antibodies. The unpublished immunohistological data of Prof. Miyata showed that all commercial antibodies (5,9) showed the positive responses in the TRPM8 2/2 mice tissues. Thus, we tried to assess the TRPM8 mRNA in the tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It could also be that, in the absence of high TST levels, TRPM8 channels are more active. Nevertheless, recent studies have shown that estrogens and their receptor have a genomic effect on TRPM8 in cancer and dermal tissue 37‐39 . The authors of two of these studies have suggested that the lack of estrogens induces TRPM8 overexpression in the skin, and therefore, hypersensitivity to cold in menopausal women 38,39 …”
Section: Discussionmentioning
confidence: 99%